Pengaruh Fear Appeals, Endoser Dan Jingle Dalam Iklan Suzuki Nex Di Televisi Versi Band Sm*Sh Terhadap Respon Konsumen - Sanjaya, Dhida Surya; Kusasih, Ida Ayu K. R. (STIE Surakarta, 2012)
Promotion is one way to introduce a product to the public. One of the media that has been chosen to conduct a campaign is advertising on television. From a variety of attractions offered by an advertisement on television such as fear appeals, endoser, and jingles.Â From attractions makes the advertisementÂ get a response from consumers